PERNIKAHAN USIA DINI DI DESA BUKIT PAYUNG KECAMATAN BANGKINANG KABUPATEN KAMPAR - ", Musalim; ", Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research titled ?early marriage in the Bukit Payung village. Then the reseacher in interested this lifting thems because the fhenomena is in society the early occur the teenagersin society in the Bukit Payung village. Data analysis answerthe problems that exsist in this study are analyzed in deskriptive qualitative that analysis how truth , the early that occur wiyhin the next society in analysis theories in the this research. (1) Factors which teenagers at an early age marriage in the Bukit Payung village. (2) How are in the application family function at an early age. In data collection in this is observation, interview, and documentation. As for the respondents in this study is 12 people or 6 pairs of respondents.The research proves that early marriage the caused by economi factor , internal factor one pairs, eksternal factor five pairs for six pairs of this one pairs caused of tradition to marriage teenagers of early age, three pairs for six pairs caused of economi be of the opinion that early marriage can family economi proped and one pairs for six pairs caused education or dropout. While of family function early age marriage do not running properly becaused of assisted by parents.Keywords : Early Marriage, Teenagers, Familly